Application of Modified-Partial Capacity Design Method on 6- and 15-story Square Buildings with Variation in number of Elastic Columns - Pamuda Pudjisuryadi; Benjamin Lumantarna; Fransisca Wijaya; C. Aphrodita; A. Jesica; Y. Karyanto; M.K. Theodora (Institute of Research and Community Outreach - Petra Christian University, 2022)
Modified-Partial Capacity Design (M-PCD) is proposed as one alternative of structural design methods. In M-PCD, the partial side sway mechanism where beams and some columns may develop plastic hinges. This method uses two structural models during the design process. The models are used to simulate undamaged and damaged structures when subjected to design earthquake (R=8.0) and larger target earthquake (R=1.6) respectively. In this study, 6- and 15-story square buildings with 30% and 50% elastic column are designed using M-PCD. Performances of the buildings are investigated by using non-linear time history analysis. Results show that the buildings’ performances are still unsatisfactory, especially for the 15-story buildings. However, it should be noted that the levels of earthquakes used for the analysis were larger than that used for the design. A more accurate prediction of the required strength should be developed further to improve M-PCD.